National Scouting Combine scores as performance predictors in the National Football League - Vincent, L. M.; Blissmer, B. J.; Hatfield, D. L. (The Journal of Strength and Conditioning Research, 2019)
The National Football League (NFL) hosts an annual scouting combine to evaluate the approximately 300 elite college football players who are most likely to be selected in the upcoming NFL draft. Given the public interest, player obligations, coaching staff commitments, and business aspects of the combine, several questions have arose in recent years concerning the applicability of combine scores to eventual draft NFL performance. The primary purpose of this study is to investigate the relationship between specified National Scouting Combine (NSC) scores and measures of performance by player position. A secondary aim was to determine whether correlated variables could predict player performance at the quarterback (QB), running back (RB), wide receiver (WR), defensive end (DE), defensive tackle (DT), and linebacker (LB) positions. Subjects in this study were combine participants between the years 2005-2010 who subsequently played in the NFL. The positional groups investigated were QBs (N = 44), RBs (N = 82), WRs (N = 116), LBs (N = 139), DEs (N = 59), and DTs (N = 72). Combine raw scores for 40-yd dash time, countermovement vertical jump (CMVJ) height, standing long jump (SLJ) distance, and pro-agility time were recorded. Measures of horizontal and vertical power were calculated for the 40-yd dash and CMVJ. Combine scores and on-field positional statistics for the first 4 years for QBs and 3 years of all other players' careers were analyzed to investigate relationships. Significant correlations were shown between at least one combine measure and on-field success at every position. Hierarchal regression showed combine measures could predict between 4% and 62% of the variance for individual on-field variables. Quarterback rushing yards were significantly correlated with 40T, CMVJ, vertical jump power (VJP), vertical jump relative power (VJRP), and horizontal power (HP), and those factors accounted for 62.2% of the total variance. Horizontal power and VJP were predictive of QB rushing attempts (r 2 = 0.370). At RB, 40T and SLJ combined were predictive of total rushing yards (r 2 = 0.200), rushing attempts (r 2 = 0.195), and yards per game (r 2 = 0.197). Power variables were predictive of total tackles for DEs' 40HP (r 2 = 0.096) and VJP (r 2 = 0.018), accounting for a total of 21% of the variance. The current study suggests that combine tests are modest predictors of future performance. Should the NFL change the current NSC testing battery, the addition of horizontal and vertical power measurements, as well as position-specific skill tests are recommended.